Analisis Semiotik Iklan Mars Perindo - Muhammad Dhaldiri Zain; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2018)
This study aims to see what the meaning of Perindo Marching adverstiment is. This study used qualitative approach and semiotics method especially television codes proposed by John Fiske that divided into three levels. They are reality, representation, and ideology levels. The result showed that the meaning of Perindo marching tune is an effort of forming its identity to the society. Perindo marching advertisement showed the realization of people prosperity by Hary Tanoesoedibyo and looked at him as the candidate who will make Indonesia to be better. Perindo advertisement was a campaign media to introduce Hary Tanoesoedibyo to the society. The positive perception in this advertisement was making Perindo and Hary Tanoesoedibjo to be known and accepted and supported by society when the political season will come.